2021
DOI: 10.3390/ijerph18158055
|View full text |Cite
|
Sign up to set email alerts
|

Be Aware of Burnout! The Role of Changes in Academic Burnout in Problematic Facebook Usage among University Students

Abstract: Most previous research has examined the relationship between FB addiction and burnout level by conducting cross-sectional studies. Little is known about the impact of changes in burnout on FB addiction in an educational context. Through a two-way longitudinal survey of a student population sample (N = 115), this study examined the influence of changes in academic burnout over time and FB motives and importance (measured at the beginning and the end of the semester) on FB intrusion measured at the end of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Another factor related to exposure to social media networks of academic burnout was found [15]. A similar finding also revealed the interaction effects between social motives on Facebook and changes in academic burnout and between the importance of Facebook and its inefficiency and burnout [17].…”
Section: Factors Associated With Academic Burnoutsupporting
confidence: 56%
“…Another factor related to exposure to social media networks of academic burnout was found [15]. A similar finding also revealed the interaction effects between social motives on Facebook and changes in academic burnout and between the importance of Facebook and its inefficiency and burnout [17].…”
Section: Factors Associated With Academic Burnoutsupporting
confidence: 56%
“…Organisations and users go to all the expense of content creation, advertising and technical resources (Tseng et al, 2022;Rajan et al, 2021). Tomaszek and Muchacka-Cymerman (2021) assert that a great deal of time is invested in managing and maintaining a presence on Facebook, in effecting regular updates, in monitoring interactions, and in responding to queries. The expertise to handle the technicalities of the platform is highlighted by Todorovic (2021) as a challenge for especially individuals and organisations with limited digital skills.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…The time it takes to compose a message proves to be a challenge to Facebook users (Tomaszek & Muchacka-Cymerman, 2021). to handle technicalities users are expected to understand the technical information-sharing dynamics before they send their messages to target users (Todorovic, 2021).…”
Section: Time Investmentmentioning
confidence: 99%
“…Our analysis showed that Internet addiction had a significant direct effect on all three dimensions of learning burnout. A longitudinal survey exhibited that the importance of social media website Facebook enhanced the prediction power of changes in the academic burnout total score, exhaustion, and personal inefficacy ( 64 ). Compared to the other dimensions, emotional exhaustion was the least significantly directly affected by Internet addiction (H1a, β = 0.115, p < 0.05), but was significantly influenced by the mediating effect of loneliness ( β = 0.347, bootstrap 95% CI [0.273, 0.424]), predominantly emotional loneliness.…”
Section: Discussionmentioning
confidence: 99%